Analisis Faktor-Faktor yang Memengaruhi Penggunaan Mobile Banking pada Pengguna Laki-laki dan Perempuan dengan Menggunakan Pendekatan Multigroup Structural Equation Modelling - Adnyani, Ni Luh Saddhwi Saraswati; Sari, Dini Hanifa; Rayani, Fouri Noviyanti; Lubis, Savira Pratidina (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2025)
Mobile banking (m-banking) allows financial services to be accessed more easily. Some studies have found differences in technology acceptance decisions between men and women. This research was conducted to analyze the factors influencing the use of m-banking among male and female users using a multigroup structural equation modeling (SEM) approach. There are seven factors or latent variables used in this study, namely word of mouth (WOM), perceived ease of use (PEOU), perceived usefulness (PU), trust (TR), attitude toward using (ATU), intention to use (ITU), and actual use (AU). Based on the testing conducted with 440 respondents' data, it was found that for male and female users there are differences in the relationship between WOM and TR, PU, ATU, and ITU; PEOU and PU; PU with ATU and ITU; and ITU with AU. This study provides additional evidence of gender differences in the acceptance and use of technology, especially m-banking. Additionally, this study found that WOM has a significant impact on the adoption of m-banking; therefore, future research should identify the factors that can influence the WOM of m-banking service customers.